PEMBENTUKAN KARAKTER RELIGIUS MELALUI BUDAYA SEKOLAH DI SD SUPRIYADI KOTA SEMARANG - Hasnan Nur Fauzi; Joko Sulianto; Ervina Eka Subekti (STKIP Subang, 2023)
This research is motivated by the scarcity of religious school culture in several schools which serves to prevent moral degradation. However, Supriyadi Elementary School in Semarang City is one of the schools that has a special program of Islamic education and school culture in the religious field which aims to improve students' religious character. This study aims to describe the school culture in SD Supriyadi Semarang City, as well as describe the formation of religious character through school culture in SD Supriyadi Semarang City. The approach used in this research is qualitative with descriptive type. Data collection techniques were carried out by interviews, observation, documentation and field notes with PPL teachers and school principals. The results showed that the school culture at Supriyadi Elementary School, Semarang, in general, included 5S habituation (smile, greet, greet, be polite, and polite), pray and read the asmaul husna before learning activities begin, pray dhuha in congregation, midday prayer, Friday prayer. 'at congregation at the mosque for male teachers and male students, tahfidzul qur'an, memorizing daily prayers, as well as commemoration of Islamic holidays. The formation of religious character at SD Supriyadi has been carried out well through the school culture that has been implemented properly and regularly by all students and teachers at SD Supriyadi, Semarang.